2010
DOI: 10.1111/j.1469-185x.2009.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Resource pulses and mammalian dynamics: conceptual models for hummock grasslands and other Australian desert habitats

Abstract: Resources are produced in pulses in many terrestrial environments, and have important effects on the population dynamics and assemblage structure of animals that consume them. Resource-pulsing is particularly dramatic in Australian desert environments owing to marked spatial and temporal variability in rainfall, and thus primary productivity. Here, we first review how Australia's desert mammals respond to fluctuations in resource production, and evaluate the merits of three currently accepted models (the ecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
111
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(123 citation statements)
references
References 192 publications
4
111
3
1
Order By: Relevance
“…My results support the hypothesis that rocky habitats represent a refuge from introduced predators for threatened northern Australian mammals and in arid environments, although they are not necessarily the highest quality habitat on other dimensions (Letnic and Dickman 2010;Start et al 2007;Woinarski et al 2011). …”
Section: Potential Sources Sinks and Habitat Quality Implications Fsupporting
confidence: 75%
See 1 more Smart Citation
“…My results support the hypothesis that rocky habitats represent a refuge from introduced predators for threatened northern Australian mammals and in arid environments, although they are not necessarily the highest quality habitat on other dimensions (Letnic and Dickman 2010;Start et al 2007;Woinarski et al 2011). …”
Section: Potential Sources Sinks and Habitat Quality Implications Fsupporting
confidence: 75%
“…Yang et al (2010) noted stronger responses for primary consumers around the world such as omnivores, granivores, and herbivores. In Australia, Letnic and Dickman (2010) noted that herbivores and omnivores responded more immediately to drought-breaking pulses than did carnivorous marsupials; Rodentia (rodents), Peramelidae (bandicoots), Potoroidae (bettongs and potoroos), and Macropodidae (kangaroos) responded more strongly than Dasyuridae (carnivorous marsupials). Similarly, in the Simpson Desert in western Queensland, Greenville et al (2016) showed that rodent abundance was tightly linked to rainfall because rodents respond opportunistically to rain at any time of year, but this was not the case for dasyurids in the genera Dasycercus, Sminthopsis, and Ningaui.…”
Section: Introductionmentioning
confidence: 99%
“…As ENSOdriven bust periods increase mammalian dispersal distances simultaneously with an increase in fire size, buffering such effects could substantially reduce mortality through both predation and resource limitation, mitigating declines and species extinction among mammals in the critical weight range (50-3,000 g), most of which have occurred in desert regions (17,26). If Aboriginal fire regimes do buffer climate-driven variability in fire size, then the deterioration of Aboriginal fire mosaics following their removal from the desert around the mid-20th century (15) likely explains observed increases in catastrophic fires and subsequent declines and extinctions of many small-to medium-sized mammal populations (27,28), and provides a strategy to mediate these effects in the future.…”
mentioning
confidence: 99%
“…However, bottom-up factors, such as food availability and habitat structure, can also influence predator-prey interactions (Ritchie & Johnson 2009). For example, resource abundance can temporarily allow prey populations to escape predator regulation and decouple interactions between predators (Letnic & Dickman 2010).…”
Section: Predator-prey Interactionsmentioning
confidence: 99%